Accumulating evidences of callose priming by indole- 3- carboxylic acid in response to Plectospharella cucumerina. (3rd July 2019) - Pastor-Fernández, J.; Pastor, V.; Mateu, D.; Gamir, J.; Sánchez-Bel, P.; Flors, V.
ABSTRACT: Indole-3-carboxylic acid (I3CA) is an indolic compound that induces resistance in Arabidopsis adult plants against the necrotrophic fungus Plectosphaerella cucumerina through primed callose accumulation. In this study, we confirm the relevance of ATL31 and SYP121 genes involved in vesicular trafficking in I3CA priming of defenses and we discard camalexin as a mediator of I3CA-induced resistance (IR) in adult plants. In addition, we observed that an intact I3CA biosynthetic pathway is necessary for I3CA-IR functionality.